2005
DOI: 10.1007/s00432-005-0674-z
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of CC3/TIP30 is associated with HER-2/neu status in breast cancer

Abstract: Our findings suggest a potential link between the expression of CC3/TIP30 gene and the HER-2/neu oncogene-mediated signal pathway.These findings could not have been predicted from previous experimental studies, and suggest that CC3/TIP30 may play a complex role in breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…In addition to these studies demonstrating the role of HER2/neu in gynecological cancers, Zhang et al . reported that overproduction of HTATIP2/TIP30 is associated with HER2/neu status in breast cancer [10]. All of these studies support our findings that HTATIP2/TIP30 has a potential role in ovarian cancer, and that HER2/neu expression may be related to increased HTATIP2/TIP30 levels.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition to these studies demonstrating the role of HER2/neu in gynecological cancers, Zhang et al . reported that overproduction of HTATIP2/TIP30 is associated with HER2/neu status in breast cancer [10]. All of these studies support our findings that HTATIP2/TIP30 has a potential role in ovarian cancer, and that HER2/neu expression may be related to increased HTATIP2/TIP30 levels.…”
Section: Discussionsupporting
confidence: 91%
“…In addition to these studies demonstrating the role of HER2/neu in gynecological cancers, Zhang et al . reported that overexpression of human HIV-1 TAT interactive protein 2 (HTATIP2/TIP30) is associated with HER2/neu status in breast cancer [10]. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, TIP30 was found to interact with coactivator independent of AF-2 function and negatively regulate estrogen receptor (ER) a-mediated c-myc expression [8]. Studies on clinical samples showed that TIP30/CC3 expression was significantly associated with positive HER-2/neu status at both mRNA and protein levels [9]. The expression profile of TIP30/CC3 in clinical specimens of cancers, especially in breast cancer, has not been well characterized.…”
Section: Introductionmentioning
confidence: 98%
“…To date, several studies have utilized RPMA in the analysis of cancer signaling pathway alterations with clinical prostate (Paweletz et al 2001; Grubb et al 2003; Herrmann et al 2003), ovarian (Wulfkuhle et al 2003; Sheehan et al 2005), colorectal (Belluco et al 2005), breast cancer (Zhang DH et al 2005a, b; Cowherd et al 2004, Wulfkuhle et al 2002; Kersting et al 2004) and lymphoma (Zha et al 2004; Gulmann et al 2005) specimens using RPMA. In these studies, pro-survival, pro-mitogenic, and cell-cycle regulatory proteins, including phospho-Akt, PI3K, ERK, MAPK, PKCα, p38, STAT1, GSK3-β, cytochrome c oxidase, c-erbB2, and c-erbB1, phospho-PTEN, EGFR, have been studied.…”
Section: Reverse Phase Protein Microarray (Rpma) In Clinical Phosphopmentioning
confidence: 99%